Diallel analysis of field resistance to brown streak disease in cassava (Manihot esculenta Crantz) landraces from Tanzania - Kulembeka, H.P.; Ferguson, Morag E.; Herselman, L.; Kanju, E.; Mkamilo, G.S.; Masumba, E.; Fregene, Martin A.; Labuschagne, Maryke T. (Springer, 2012)
Cassava brown streak disease (CBSD) is an economically important virus disease causing significant losses to cassava root yield and quality in east, central and southern Africa. Breeding for resistance in cassava requires an understanding of the underlying genetic control of CBSD resistance. Sources of CBSD resistance are available but little is known on the value of those varieties as parents for CBSD resistance breeding. Two resistant and two susceptible varieties were crossed in a half diallel design and 35 F1 progeny from each of the six families, plus parents, were screened at two locations in a randomised complete block design with four replications in warm sub-humid environments of coastal Tanzania in 2008. Screening for CBSD field resistance was done using disease severity scoring on a scale of 1–5. Significant variations in disease severity were observed for crosses, general combining ability (GCA) and specific combining ability (SCA) at both locations. The CBSD shoot symptom severity scores ranged from 1 to 4.4 while root necrosis ranged from 1.3 to 4.5. The contribution of GCA to the total sum of squares of crosses for disease scores ranged from 86.9 to 95.2 % compared to SCA that ranged from 4.8 to 14.2 %. Additive gene effects were more important than non-additive effects indicating that CBSD resistance is genetically determined and that selection should be successful to improve resistance. Selection of parents with good GCA effects will be important for success in CBSD resistance breeding.